2015
DOI: 10.1039/c5tb01027f
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional PEG–PLL drug conjugate forming redox-responsive nanoparticles for intracellular drug delivery

Abstract: Tumor-targeted, redox-responsive and high drug-loaded nanoparticles were synthesized from poly(ethylene glycol)-bpoly(L-lysine) (PEG-PLL) for enhanced cancer therapy. Hydrophobic drug camptothecin (CPT) was anchored to the lysine residual amines in PEG-PLL via disulfide bonds. Folate acid as targeting group was further introduced to the PLL block via long PEG chains. The conjugate self-assembled into nanoparticles of around 100 nm with hydrophobic CPT moieties forming the core and folate acid targeting groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…When analyzed using the MCF‐7 breast cancer cell line, PEG 45 ‐P(L‐Lys), PEG 45 ‐P(L‐Lys) 25 ‐CPT 6 , and PEG 45 ‐P(L‐Lys) 25 ‐SS‐CPT 6 (additionally incorporated disulfide bond) displayed IC 50 values of 500.0, 6.8, and 0.88 μg mL −1 , respectively. In general, conjugates were more active against OVCAR‐3 cell line and less active against MCF‐7, SKOV‐3, and MDA‐MB‐468 cells when compared with free CPT …”
Section: Physico‐chemical Properties Driving the Bio‐nano Interfacesupporting
confidence: 81%
See 2 more Smart Citations
“…When analyzed using the MCF‐7 breast cancer cell line, PEG 45 ‐P(L‐Lys), PEG 45 ‐P(L‐Lys) 25 ‐CPT 6 , and PEG 45 ‐P(L‐Lys) 25 ‐SS‐CPT 6 (additionally incorporated disulfide bond) displayed IC 50 values of 500.0, 6.8, and 0.88 μg mL −1 , respectively. In general, conjugates were more active against OVCAR‐3 cell line and less active against MCF‐7, SKOV‐3, and MDA‐MB‐468 cells when compared with free CPT …”
Section: Physico‐chemical Properties Driving the Bio‐nano Interfacesupporting
confidence: 81%
“…The assessment of a series of CPT conjugated PEG 5000 ‐P(L‐Glu) graft‐copolymers demonstrated that an increased CPT content led to an increase in final nanosystem size from 30 nm (15.2 wt% of CPT) to 65 nm (25.1 wt% of CPT) . Zhou et al obtained similar results for a synthesized series of PEG 45 ‐P(L‐Lys) 25 ‐SS‐CPT x ( x = 3, 6, and 8), where all of the conjugates formed spherical particles with diameters of 85, 118, and 152 nm, respectively . Analogous trends were observed for other hydrophobic drugs such as Dox .…”
Section: Physico‐chemical Properties Driving the Bio‐nano Interfacementioning
confidence: 63%
See 1 more Smart Citation
“…Self‐assembled drug delivery systems (sDDSs) such as polymeric micelles, liposomes, vesicles, and cationic polymer/nucleic‐acid complexes (polyplexes) have received enormous attentions in pharmaceutics, particularly in cancer treatment . sDDS's advantages include significantly improved water solubility, and thus administration of hydrophobic drugs, enhancing tumor accumulation via tumors' enhanced permeation and retention (EPR) effect and possibly receptor‐specific interactions between the target cells and the nanocarriers …”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-based upconversion nanoparticles (UCNPs) have been widely investigated for biological applications, including bioimaging, biomolecular sense, and photodynamic therapy, [1][2][3] because they can provide visible or near-infrared emission under excitation at 980 nm wavelength and exhibit (2 of 10) 1700090 just endow these nanoparticles with water solubility or single stimuli for drug delivery, which cannot be used for effective diagnosis and treatment. [17][18][19][20] To work out this issue, intelligent drug delivery systems have recently gained great attention because of their controllable on demand release of anticancer drugs in response to intracellular microenvironmental stimuli, including pH, light, redox, and enzyme, [21][22][23][24] producing stronger anticancer activity with fewer side effects. Particularly, pH-/redoxresponses have drawn much attention for drug delivery because tumors usually have the lower pH value and higher glutathione (GSH) than normal tissue.…”
Section: Introductionmentioning
confidence: 99%